ANALISIS KUALITAS PELAYANAN DENGAN PENDEKATAN MODEL CARTER PADA BPRS MUAMALAT HARKAT SUKARAJA - Kustin Hartini; Gita Meilani (Jurnal Bisnis, Manajemen, dan Akuntansi, 2019)
The purpose of this study was to determine the effect of the CARTER model on service quality at the BPRS Muamalat Harkat Sukaraja. The sampling technique used was purposive sampling. Data collection techniques in this study used primary data by distributing 98 questionnaires and using quantitative approaches. The questionnaire was processed by conducting a validity and reliability test. The data analysis method uses multiple linear analysis with the help of SPSS. From the analysis results obtained a regression equation Y = 1.189 + 0.129X1 + 0.115X2 + 0.113X3 + 0.271X4 + 0.021X5 + 0.247X6 + e. T Test results prove that the variable compliance (X1), assurance (X2), reliability (X3), tangibility (X4), empathy (X5), responsiveness (X6) significantly influence the quality of service at BPRS Muamalat Harkat Sukaraja, as well as Simultaneously with the F Test shows the overall variables together significantly influence the quality of service at BPRS Muamalat Harkat Sukaraja. Overall the independent variables used in this study showed a strong influence with an R Square value of 60.4% while the remaining 39.6% were influenced by the independent variables not included in the study